2020
DOI: 10.3390/fluids5010014
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Swimmers in Fluids with Resistance

Abstract: Micro-swimmers such as spermatozoa are able to efficiently navigate through viscous fluids that contain a sparse network of fibers or other macromolecules. We utilize the Brinkman equation to capture the fluid dynamics of sparse and stationary obstacles that are represented via a single resistance parameter. The method of regularized Brinkmanlets is utilized to solve for the fluid flow and motion of the swimmer in 2-dimensions when assuming the flagellum (tail) propagates a curvature wave. Extending previous s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…Mathematical models for flagellar swimming in groups are an active area of research. Some studies have considered 2D fluids, which demonstrated a tendency of flagella to attract and that this attraction is energetically favorable [23,[28][29][30]. In 3D fluids, models have shown both attraction and repulsion of neighboring flagellar pairs, but the results are dependent on configurations of the flagella, the fluid domain, timescales of simulation, and the flagellar model.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Mathematical models for flagellar swimming in groups are an active area of research. Some studies have considered 2D fluids, which demonstrated a tendency of flagella to attract and that this attraction is energetically favorable [23,[28][29][30]. In 3D fluids, models have shown both attraction and repulsion of neighboring flagellar pairs, but the results are dependent on configurations of the flagella, the fluid domain, timescales of simulation, and the flagellar model.…”
Section: Introductionmentioning
confidence: 99%
“…Recent work has simulated flagella in pairs for up to 10-20 beats [35] but we will go beyond this here to address any lingering questions about long-range stability of flagellar interactions like those posed in [30]. Simulations involving all of these components are computational expensive due to the finer scale details we aim to resolve but they are plausible, as long as we relax some of other ideal features of a model.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…We also revisit the classic problem of lid-driven cavity flows ( 33 35 ), now containing an immersed deformable sphere, and provide detailed data to serve as benchmarks. There has been sustained interest in swimming and biolocomotion in recent decades, yet reduced-dimension models of the swimmer ( 36 38 ) are often the state of the art. We present a model of a swimming organism using full volumetric actuation, demonstrating the RMT as a simulation tool for exploring a broader range of swimming modalities.…”
mentioning
confidence: 99%